The orchard of lost souls - Mohamed, Nadifa 1981- (Simon & Schuster, 2014)
"It is 1988 and in Somalia whispers of revolution travel on the dry winds. Soon, and through the eyes of three women, we will see the country fall. Nine-year-old Deqo has left the vast refugee camp she was born in, lured to the city by the promise of her first pair of shoes. Kawsar, a solitary widow, is trapped in her little house with its garden clawed from the desert, confined to her bed after a savage beating in the local police station. Filsan, a young female soldier, has moved from Mogadishu to suppress the rebellion growing in the north. And as the country is unravelled by civil war their lives will change forever..." Klappentext
Keywords: Somalia--History--1960-1991--Fiction.; Fiktionale Darstellung